KARAKTERISTIK ENDAPAN NIKEL LATERIT PADA BLOK X PT. BINTANGDELAPAN MINERAL KECAMATAN BAHODOPI KABUPATEN MOROWALI PROVINSI SULAWESI TENGAH (Jurnal Geomine, 2015)
Deposit of laterite nickel formed by intensive weathering at tropical area, specially containing of rock element of Ni like peridotite and serpentinite, influenced by bedrock, climate, chemical reagen-reagen and vegetasi, geology structure, topography, and also time. The intention of the research it’s to knowing the characteristics of laterite nickel deposit. The method of the research used by descriptive analyse method pursuant to primary data in the form the vegetation, the morphology, litology on the surface, data of longging core, and chemical data a assay. And also data sekunder in the form of supporter data that is analyse the petrografi bedrock. The result of analyse of mineralogy of drilling sample the zona deposit of nickel laterite of research area composed by the limonit dominated by of hematite and goetite mineral, a saprolit dominated by serpentine grup and bedrock dominated by olivine and piroxen minerals. The result of perception of petrografi bedrock come from peridotite composed by olivine, piroxen minerals, serpentine, and opaque mineral. Conclusion obtained from this research is rich laterite type of element of Ni that is redish brown laterite come from ultramafik rock, there are at morphology the slope is 10°-30°, vegetation dominated in the form of clump crop, and coppice, obstetrical of element Ni at the saprolite own the mean deepness 7-20 metre, obstetrically Ni is Mean >1%.